2022
DOI: 10.3390/su14127500
|View full text |Cite
|
Sign up to set email alerts
|

The Determinants of Impulsive Buying Behavior in Electronic Commerce

Abstract: Consumers’ online impulsive buying behavior has become more and more frequent in the digital era. There is increasing concern regarding the adverse consequences that impulsive buying has generated for consumer wellbeing and the sustainability of our society and environment. In search of a way to decreasing impulsive consumption, this article proposes a comprehensive framework to explore the potential determinants of online impulsive buying behavior from the perspective of consumer characteristics grounded on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
3
9

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 89 publications
(146 reference statements)
0
14
3
9
Order By: Relevance
“…Surprisingly, Study 2 revealed that Instagram comments and reviews did not significantly affect positive emotions, contrary to Study 1 and previous research findings (Zhang et al, 2018;Zhao et al, 2021). The present study's findings challenge prior research suggesting that individuals from collectivist communities are more prone to impulsive purchasing activities influenced by significant others (Miao et al, 2019;Wang et al, 2022). The focus group discussions suggested that fabricated comments and reviews might have contributed to this outcome, raising concerns about their authenticity and influence.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, Study 2 revealed that Instagram comments and reviews did not significantly affect positive emotions, contrary to Study 1 and previous research findings (Zhang et al, 2018;Zhao et al, 2021). The present study's findings challenge prior research suggesting that individuals from collectivist communities are more prone to impulsive purchasing activities influenced by significant others (Miao et al, 2019;Wang et al, 2022). The focus group discussions suggested that fabricated comments and reviews might have contributed to this outcome, raising concerns about their authenticity and influence.…”
Section: Discussioncontrasting
confidence: 99%
“…Impulsive purchasing, characterized by compulsiveness, can be a potential strategy for escaping negative emotional states (Ahn and Kwon, 2022). Given the wide range of products available in social commerce, customers are more likely to engage in impulsive purchasing to alleviate their negative feelings (Wang et al, 2022). Based on these insights and the qualitative findings, the present study proposes the following hypothesis:…”
Section: Figure 2 Hypothesized Modelmentioning
confidence: 89%
See 1 more Smart Citation
“…IB is characterized with 1. making rapid or instant purchase decisions (Verplanken & Herabadi, 2001;Foroughi, Buang, Senik, & Hajmisadeghi, 2013) 2. subjective bias in favour of immediate possession (Rook & Gardner, 1993). Almost 80 percent of buyers have IB behaviour (Bellenger, Robertson, & Hirschman, 1978;Han, Morgan, Kotsiopulos, & Kang-Park, 1991;Hausman, 2000) which data justifies the importance of maintaining, even improving, and creating the factors influencing impulse purchase behavior (Wang, Pan, Xu, Luo, & Wu, 2022), especially the developing economies like Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Most extant researchers (e.g., Han, Morgan, Kotsiopulos, & Kang-Park, 1991;Hausman, 2000;Foroughi, Buang, Senik & Hajmisadeghi, 2013;Saad & Metawie, 2015;Wang, Pan, Xu, Luo & Wu, 2022) have focused on distinguishing impulsive buying behavior from non-impulsive buying behavior, with a number of determinants of impulsive buying behavior. Only a very few studies have focused on in-store attributes like employees' caring behavior and the physical environment (Saad & Metawie, 2015) of the store like display (Gorji & Siami, 2020), music (Grewal, Baker, Levy & Voss, 2003;, sales person's behavior (Goff, Boles, Bellenger & Stojack, 1997), and music and scent .…”
Section: Introductionmentioning
confidence: 99%